2022
DOI: 10.4102/sajpsychiatry.v28i0.1550
|View full text |Cite
|
Sign up to set email alerts
|

Mental health distress during the COVID-19 pandemic in Nigeria: Need for psychological intervention

Abstract: Setting: Community-based study covering the North, South and West of Nigeria.Methods: This was a descriptive cross-sectional study using an on-line survey form via the snowballing sampling method.Results: Social media was identified as the main source of information concerning COVID-19, and half of the respondents opined that information dissemination was inadequate. Psychological distress was present in 90.5% of the participants and 61.8% admitted that this distress was worsened by fake news and myths concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The second research generated satisfying results to declare objectives achievement considered relevant for COVID-19 pandemic studies [43,56,57]. The perceptions of the interviews regarding the impact of the pandemic were identified (O 2 ), the participants declaring the feelings of fear increasing or unpleasant experiences intensifying, and even behavioral changes in buying frequency (less often), or more often in the case of purchasing preventive drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second research generated satisfying results to declare objectives achievement considered relevant for COVID-19 pandemic studies [43,56,57]. The perceptions of the interviews regarding the impact of the pandemic were identified (O 2 ), the participants declaring the feelings of fear increasing or unpleasant experiences intensifying, and even behavioral changes in buying frequency (less often), or more often in the case of purchasing preventive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…On the above-mentioned aspects can be added the fact that myths, inaccurate information, and the phenomenon of "fake news" about COVID-19 have spread extremely rapidly in both traditional media and social media, with a negative impact on the mental health of individuals [43,56,57]. Fears about the transmission of the virus, the illness itself, or the experience of the disease lived by a family member or close acquaintance have an impact on the mental functions of human nature.…”
Section: Covid-19 and Mental Healthmentioning
confidence: 99%
“… 11 - 14 In addition, The enforced isolation, disruption of familiar routines, and limited social interactions have contributed to increased cognitive decline, heightened anxiety, and exacerbated behavioral symptoms among dementia patients. 12 , 15 - 18 Social workers, acting as crucial intermediaries, encountered heightened stress, burnout, and emotional fatigue due to the intensified demands of remote care and the inherent emotional toll of witnessing the deterioration of their clients’ mental health. 8 Social isolation, a key preventive measure, resulted in decreased social engagement, exacerbating cognitive decline and behavioral symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…On March 11, 2020, the World Health Organisation (WHO) declared the outbreak a pandemic. The latest figures reported by the World Health Organization (WHO) state that 212 countries in the world have been affected, with around 1,356,780 positive cases and 79,385 deaths recorded due to this outbreak (Adiukwu et al, 2022) The outbreak is caused by a new variant of the influenza virus known as the coronavirus, with the official name for the disease being Covid-19 (Susilo et al, 2020). This type of virus variant is relatively new.…”
Section: Introductionmentioning
confidence: 99%
“…This virus can be detected in the feces, and it is reported that 23% of patients reported that the virus remains detected in the feces even though it is not detected in the airway sample. SARS-CoV-2 infects cells in the airway lining the alveoli in humans (Adiukwu et al, 2022;Susilo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%